Applied Fundamentals in Finance: Portfolio Management and Investments - Mondello, Enzo (Springer, 2024)
This textbook provides a comprehensive introduction to portfolio management and investments. Focusing on four core areas - portfolio management, equities, bonds, and derivatives - it is primarily intended for undergraduate and graduate students alike.